2010
DOI: 10.1177/1090820x10374724
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Singulair (Montelukast) Treatment for Capsular Contracture

Abstract: Our preliminary study shows that Singulair improves CC. Breasts with mild CC (Baker score < III) appeared to have better improvement with Singulair compared to those with more severe contracture (Baker score III and IV). Singulair is well tolerated with minimal side effects and can be administered to patients after breast implant surgery to improve CC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 17 publications
1
35
0
1
Order By: Relevance
“…This suggests that montelukast had a prophylactic effect against capsular contracture. This finding is supported by a study in breast augmentation patients which similarly showed that montelukast significantly reduced post‐operative capsular contracture formation . The capsule cut measurements also demonstrated 9°more extension of the operative limb over the rats in CTL.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This suggests that montelukast had a prophylactic effect against capsular contracture. This finding is supported by a study in breast augmentation patients which similarly showed that montelukast significantly reduced post‐operative capsular contracture formation . The capsule cut measurements also demonstrated 9°more extension of the operative limb over the rats in CTL.…”
Section: Discussionsupporting
confidence: 64%
“…Being a leukotriene receptor antagonist, montelukast can inhibit the inflammatory cascade and might prevent fibrosis. It has been shown that prophylactic use of montelukast decreased capsular contracture in patients following breast augmentation …”
mentioning
confidence: 99%
“…6567 Other research groups modulated the effects of the inflammatory pathway to reduce fibrosis and contracture using pirfenidone that inhibits TGFβ synthesis, enalapril that negates the fibrotic and inflammatory effects of angiotensin II, tumor necrosis factor–stimulated gene 6 overexpression (which provides an anti-inflammatory effect via modulation of hyaluronan), and the anti-inflammatory medications zafirlukast and montelukast. 20,44,6870 Although these studies have been performed using only small numbers of animals, they strongly suggest a link between inflammation and capsular contracture.…”
Section: Discussionmentioning
confidence: 99%
“…Montelukast, which was used to reduce the occurrence of capsular contracture [9], is a leukotriene antagonist which binds to leukotriene receptors. Thus, by inhibiting the activation of leukotriene, it plays a role in reducing the occurrence of inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%